Protein and Carbohydrate Profiling of Fermented Ambali (Pithecellobium dulce) and Ginger Beer (Zingiber officinale): Exploring Nutritional Parameters through Probiotic Microflora - Pednekar, Manasi V.; Bande, Swati (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This research explores the nutritional exploration of two traditional fermented beverages, Ambali and Ginger beer, offering the amount of protein, carbohydrate. Employing laboratory techniques, including spectrophotometry, nutritional analysis was estimated. Our findings reveal that Ambali, crafted from finger millet through natural fermentation, has 18.04 mg/ml of protein,1.29 mg/ml carbohydrate. In contrast, Ginger beer showed protein estimation of < 1mg/ml , 4.9g/100ml carbohydrate. Ambali has a cooling effect on body, it also aids in weight loss, has high protein and fiber content and also is rich in good bacteria. On the other hand Ginger beer provides antioxidants, anti- inflammatory benefits. This research not only provides valuable insights into the nutritional qualities of Ambali and Ginger beer but also considers the potential health implications of consuming these fermented drinks. Homemade Ambali, being prepared traditionally, tends to have minimal or no added sugars making it an good option. In contrast, commercial Ginger beer may contain added sugars, impacting its overall nutritional profile.